Profesionalisme Jurnalis Dalam Film The Bang-Bang Club Berdasar Analisis Semiotika Roland Barthez - Muhammad Lutfi; Warto Warto (Jurnal Visi Komunikasi, 2020)
The Bang Bang Club is a 2011 film with a drama genre adapted from real events experienced by 4 war photographers. This film by director Steven Silver does not only cover drama but also shows how the 4 photographers actually experienced what happened. The subjects of this research were the four war photographers who were told in the film The Bang-Bang Club. Primary data is obtained from scenes related to the professionalism of a journalist in covering and reporting an event as the initial process of analysis. The scenes were analyzed using Roland Barthes' semiotics which is associated with professionalism according to Islam, in this case, namely holding the four characteristics of Raulullah, namely Sidiq, Amanah, Fathonah and Tabligh. Several scenes show the journalist in a dangerous situation, close to fire, sharp weapons, fighting, firearms, and others. The meaning of connotation means that in any situation and condition, a journalist must be able to describe, report, and collect data in any way in accordance with the journalistic code of ethics, because this has become a demand for a journalist.